Selecting Suitable Reference Gene for RT-qPCR Normalization in FFPE Breast Cancer Tissues for Duhok/Iraqi Women - S. Mohammed, Sada; AL-Mahmoodi, Hanaa; I. Yalda, Mayada (Al-Nahrain Journal of Science, 2024)
Nowadays, with the continuously increasing advances in understanding cancer system biology. It has led to the discovery of valuable disease-specific biomarkers. By targeting these markers using molecular-based techniques a highly specific and sensitive measurements can be obtained. Molecular diagnosis through PCR-based methods and next-generation sequencing (NGS) can detect many diseases caused by DNA and RNA changes that cannot be detected through antibody-based techniques. RT-qPCR is a valuable tool in measuring biomarker’s transcriptional signature and will have a great potential in personalized medicine or molecular diagnostics. In related gene expression analysis, using a suitable reference gene is crucial for the accurate interpretation of the results. For this reason, ref. gene should be validated for particular tissue, cell and experimental conditions. This study was conducted to identify and validate the most suitable housekeeping gene (HKG) as a reference (ref.) gene to obtain accurate normalization for AXL receptor tyrosine kinase gene expression in Formalin-Fixed Paraffin-Embedded “FFPE” of breast cancer tissues. Based on the five different statistical algorithms used, ACTB was the least variable ref. gene and ꞵ-GLOBIN showed the highest variability. Norm finder, Best Keeper and the comparative ΔCt method suggested to use ACTB as a ref. gene in our experiment while geNorm suggested to use the combination of both ACTB and UBC since they had the same exact stability value. In conclusion, Reffinder suggested that ACTB had the least geomean of ranking values of the four used methods showing the least variance among the other genes and the three groups of our samples.